Genomic Features and Clinical Characteristics of Adolescents and Young Adults With Cholangiocarcinoma - Feng, Hao; Tong, Huan; Yan, Jiayan; He, Min; Chen, Wei; Wang, Jian (Frontiers in Oncology, 2020)
Adolescents and young adults (AYAs) diagnosed with cancer between ages 15~45 years may exhibit unique biologic and genomic characteristics as well as clinical features, resulting in differences in clinical characters and drug resistance. However, compared to other solid cancers, relatively few studies have been conducted in this age group in cholangiocarcinoma (CCA). This study is to investigate the clinical and molecular features of AYAs with CCA. Three cohorts, including the external dataset (TCGA and MSKCC) and the perihilar CCA databank of Chinese tertiary hospitals, were contained in this study. Pathway and process enrichment analysis had been carried out with the following ontology sources: KEGG Pathway, GO Biological Processes, Reactome Gene Sets, Canonical Pathways, and CORUM. Metascape and GEPIA datasets were used for bioinformatic analysis. P< 0.05 was considered statistically significant. All statistical analyses were performed with GraphPad Prism (version 7.0; GraphPad Software, La Jolla, California) and R studio (version 3.6.1; R studio, Boston, Massachusetts). Compared to older adults, AYAs with CCA presented with worse overall survival, though the difference was not significant. Specific to patients with stage IV CCAs who underwent chemotherapy, AYAs were associated with significantly poorer OS (Fig.1B. p=0.03, HR 3.01, 95%CI 1.14~4.91). From the anatomical perspective, more eCCA was detected in the AYA group. MSI occurred in 3% of older patients in the present study. Nevertheless, none of the AYAs had MSI status. Here in this study, AYAs gained an enhanced frequency of ASXL1(p=0.02) and KMT2C(p=0.02) mutation than their older counterparts. Besides ASXL and KMT2C, the genes enriched in AYAs with CCA were analyzed by pathway and process enrichment analysis. And those genes were found to be associated with poorer differentiation, deubiquitination, and WNT signal pathway. Moreover, AYAs were relevant to poor differentiation and advanced tumor stage. This study offered a preliminary landscape of the clinical and molecular features of early onset biliary cancers. Further studies including more samples are essential to investigate whether ASXL1 and KMT2C could be considered as potentially targetable genomic signatures for young patients.